2004
DOI: 10.1289/ehp.7296
|View full text |Cite
|
Sign up to set email alerts
|

Renal Toxicogenomic Response to Chronic Uranyl Nitrate Insult in Mice

Abstract: Although the nephrotoxicity of uranium has been established through numerous animal studies, relatively little is known about the effects of long-term environmental uranium exposure. Using a combination of conventional biochemical studies and serial analysis of gene expression (SAGE), we examined the renal responses to uranyl nitrate (UN) chronic exposure. Renal uranium levels were significantly increased 4 months after ingestion of uranium in drinking water. Creatinine levels in serum were slightly but signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…Gagnaire et al [54] measured the immune biomarker enzyme phenoloxidase-like (PO) activity in zebrafish and found increased PO activity in adult fish after 48 h exposure to U, but significantly decreased PO activity in 96 h larvae after 4 d exposure to U. In mammals, Taulen and colleagues [55] found a group of genes associated with immune functions including tumor necrosis factor alpha-induced protein 1 (TNFAIP1) to be up-regulated in mouse kidney after a 48 h intraperitoneal injection exposure of 5 mg/kg uranyl nitrate. An in vitro gene expression study on murine macrophages and CD4+ T-cells showed that U induced multiple genes related to signal transduction, neurotrophic factors, chemokine and chemokine receptors, and interleukins, suggesting the immune modulation ability of U [56].…”
Section: Discussionmentioning
confidence: 99%
“…Gagnaire et al [54] measured the immune biomarker enzyme phenoloxidase-like (PO) activity in zebrafish and found increased PO activity in adult fish after 48 h exposure to U, but significantly decreased PO activity in 96 h larvae after 4 d exposure to U. In mammals, Taulen and colleagues [55] found a group of genes associated with immune functions including tumor necrosis factor alpha-induced protein 1 (TNFAIP1) to be up-regulated in mouse kidney after a 48 h intraperitoneal injection exposure of 5 mg/kg uranyl nitrate. An in vitro gene expression study on murine macrophages and CD4+ T-cells showed that U induced multiple genes related to signal transduction, neurotrophic factors, chemokine and chemokine receptors, and interleukins, suggesting the immune modulation ability of U [56].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies focused on the expression of only a few cytokine genes such as interleukins, NF- κ B , or TNF- α. Global gene expression analysis in kidney tissue after DU exposure suggested that genes involved in multiple biologic functions, including signal transduction, may be altered by uranium exposure (Taulan et al 2004). We further asked what effects DU might have on the immune system if the exposure scenario were nonlethal and long term and how it might relate to cytokine gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Biological effects of uranium in kidneys were reported, including modifications in renal metabolism of xenobiotics (Souidi et al 2005), vitamin D homeostasis (Tissandie et al 2007), and iron homeostasis (Berradi et al 2008). Excessive iron accumulation and apoptosis in the tubulointerstitial region and uranium-induced oxidative stress were reported (Linares et al 2006; Taulan et al 2004). Histological lesions of renal tissue were also observed, mainly in the cortical part of the kidneys (Donnadieu-Claraz et al 2007; Gilman et al 1998; Ortega et al 1989).…”
Section: Biological Effects and Action Mechanismsmentioning
confidence: 99%